Augmented Reality Textbook - Ngu , Cheng En (IRC, 2015)
Textbooks have wide and varied definitions and one of the common definition is that a textbook is a printed and bound artifact for every different course or branch of study (Encyclopedia of Education, 2008a). It is important and the major resource in education. However, despite of the abundance of knowledge, fact and ideas available inside the textbook, textbooks are not appreciated by most of the new generation, the gen Y or the Millenials. The Millennials are the generation who grew up surrounded by technological advances such as smartphones, computers, internet, etc. Therefore, they're tend to use different approaches to learn something instead of relying on the textbooks. Traditional textbooks are unable to captivate the interest of the Millennials because it is unable to provide the interactive learning experience like what technology provided. Therefore, an augmented reality (AR) textbook will be developed to increase textbook interactivity. A survey had been conducted on students inside the target age group which is from 17 to 24 years old. From the data collected, majority of the students participated in the survey chose videos and pictures over words as their preferable study medium. In addition to that, majority of them own at least a smartphones or tablets. These results suggests that augmented reality textbook has huge potential in education as it includes both video and picture and the function is supported by smart devices.